2023
DOI: 10.1021/acs.inorgchem.3c00743
|View full text |Cite
|
Sign up to set email alerts
|

“One-Pot” In Situ Tandem Reaction─Dy(III) Coordination-Catalyzed Multicomponent Condensation of Salicylaldehyde Derivatives to Obtain Ketals

Abstract: It is difficult to subject simple reaction starting materials to a “one-pot” in situ tandem reaction without post-treatment under mild reaction conditions to obtain multimers with complex structural linkages. In organic synthesis, acetal reactions are often used to protect derivatives containing carbonyl functional groups. Therefore, acetal products tend to have very low stability, and performing multi-step condensation to obtain complex multimeric products is difficult. Herein, we achieved the first efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Recently, coordination-driven in situ tandem reactions have attracted extensive research attention owing to their facile synthetic procedures, high reaction yields, and high atom utilization. After the metal ions participate in the coordination, multistep catalytic organic reactions occur to form complex organic ligands that are difficult to achieve using traditional one-step organic synthesis procedures. Although some progress has been made, further research is still required to gain a deeper understanding of these in situ coordination-catalyzed tandem reactions to establish specific rules to guide their precise control. Owing to its rapid detection ability, high precision, and simple operation, HRESI-MS has become the tool of choice to explore complex tandem reactions under one-pot conditions. To deeply explore the pinacol ligands in the PyraLn structure, the pinacol coupling reaction, i.e., the McMurry coupling reaction, of 2-pyrazinecarbaldehyde assisted by the Ln­(III) ion was conducted (Figure S6). After the reaction process was experienced for 24 h, the reaction solution was subjected to an electron paramagnetic resonance (EPR) test, and the experimental results showed that obvious signal peaks were detected, which proved the formation of a free radical coupling process in the reaction solution (Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, coordination-driven in situ tandem reactions have attracted extensive research attention owing to their facile synthetic procedures, high reaction yields, and high atom utilization. After the metal ions participate in the coordination, multistep catalytic organic reactions occur to form complex organic ligands that are difficult to achieve using traditional one-step organic synthesis procedures. Although some progress has been made, further research is still required to gain a deeper understanding of these in situ coordination-catalyzed tandem reactions to establish specific rules to guide their precise control. Owing to its rapid detection ability, high precision, and simple operation, HRESI-MS has become the tool of choice to explore complex tandem reactions under one-pot conditions. To deeply explore the pinacol ligands in the PyraLn structure, the pinacol coupling reaction, i.e., the McMurry coupling reaction, of 2-pyrazinecarbaldehyde assisted by the Ln­(III) ion was conducted (Figure S6). After the reaction process was experienced for 24 h, the reaction solution was subjected to an electron paramagnetic resonance (EPR) test, and the experimental results showed that obvious signal peaks were detected, which proved the formation of a free radical coupling process in the reaction solution (Figure S7).…”
Section: Resultsmentioning
confidence: 99%